The Role of Long-Range Connectivity for the Characterization of the Functional–Anatomical Organization of the Cortex - Knösche, Thomas R.; Tittgemeyer, Marc (Frontiers in Systems Neuroscience, 2011)
This review focuses on the role of long-range connectivity as one element of brain structure that is of key importance for the functional-anatomical organization of the cortex. In this context, we discuss the putative guiding principles for mapping brain function and structure onto the cortical surface. Such mappings reveal a high-degree of functional-anatomical segregation. Given that brain regions frequently maintain characteristic connectivity profiles and the functional repertoire of a cortical area is closely related to its anatomical connections, long-range connectivity may be used to define segregated cortical areas. This methodology is called connectivity-based parcellation. Within this framework, we investigate different techniques to estimate connectivity profiles with emphasis given to non-invasive methods based on diffusion magnetic resonance imaging (dMRI) and diffusion tractography. Cortical parcellation is then defined based on similarity between diffusion tractograms, and different clustering approaches are discussed. We conclude that the use of non-invasively acquired connectivity estimates to characterize the functional-anatomical organization of the brain is a valid, relevant and necessary endeavor. Current and future developments in dMRI technology, tractography algorithms and models of the similarity structure hold great potential for a substantial improvement and enrichment of the results of the technique.